Analysis of Promotional Factors and Products on Consumer Satisfaction in Wingstop Restaurant Ahmad Dahlan Jakarta - Ardi Mularsari; Feni Nurmania (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Promotion and Products are an important component in running a business and the satisfaction of consumers who buy it, Wingstop is a retail that serves food and beverages with the concept of fast food. This type of quantitative research with slovin data sample or 100 respondents with multiple linear regression analysis method. The results of the study found that Promotional and Product Factors had a significant effect on Consumer Satisfaction with Wingstop Ahmad Dahlan Jakarta.